Study of Association of Vitamin D Receptor Gene Polymorphisms with Diabetic Nephropathy - Bhuiya Esha; Saravanan Yogaprabhu; Janaki Sneha; Karthick Vijayalakshmi; Viswanathan Mohan; Venkatesan Radha; Dhanasekaran Bodhini (Journal of Diabetology)
Abstract Background: Type 2 diabetes leads to many microvascular complications, including diabetic nephropathy, also referred to as diabetic kidney disease. Vitamin D deficiency may play a role in the development of type 2 diabetes and nephropathy. The functions of vitamin D are mediated through vitamin D receptor (VDR). Three single nucleotide polymorphisms (SNPs) in VDR gene, namely, TaqI (rs731236), ApaI (rs7975232), and BsmI (rs1544410), have been widely studied in association with diabetes and nephropathy. The objective of this study was to investigate the association of these VDR gene SNPs with nephropathy in the South Indian population. Additionally, the effect of VDR gene variants on vitamin D levels was also investigated. Subjects and Methods: Two hundred forty-eight individuals with type 2 diabetes without nephropathy (T2DM) and 399 individuals with type 2 diabetes with nephropathy (T2DN) were genotyped for this study. Genotyping of TaqI was performed using the polymerase chain reaction-restriction fragment length polymorphism method. BsmI and ApaI were genotyped using MassArray. Anthropometric and biochemical data were collected for all participants. Vitamin D levels were measured in a subset of 47 T2DM and 74 T2DN individuals. Statistical analysis was performed using Statistical Package for the Social Sciences version 21.0 (IBM Corporation, Armonk, NY). Results: The genotype and minor allele frequencies of TaqI, BsmI, and ApaI were not significantly different between T2DM and T2DN groups. However, vitamin D levels were significantly reduced in T2DN (15.5 ± 1.16 ng/ml) compared to T2DM (20.5 ± 2.11 ng/ml, P = 0.027). No significant differences were found in the vitamin D levels when the T2DM and T2DN groups were stratified based on TaqI, BsmI, and ApaI genotypes. Conclusion: This study did not find a significant association of VDR SNPs (TaqI, BsmI, and ApaI) with T2DN. However, the study suggested a protective role of vitamin D levels in T2DN.